2015
DOI: 10.4102/rw.v6i1.52
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between self-efficacy and reading proficiency of first-year students: An exploratory study

Abstract: Self-efficacy, which is the belief about one’s ability to perform a task successfully, has been widely acknowledged as important in learning. This affective factor, though not explicitly evident, has been said to play an important role in academic performance. However, its role in reading development has not been widely investigated. To determine the relationship between self-efficacy and reading proficiency, a study was conducted with first-year students in a South African tertiary institution. Students’ self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 26 publications
4
24
0
6
Order By: Relevance
“…Self-efficacy is the affective variant of strategy use and they both influence reading proficiency levels considerably (Boakye, 2015a). High self-efficacy promotes metacognitive awareness and contributes to reading proficiency.…”
Section: Self-efficacy In Readingmentioning
confidence: 99%
“…Self-efficacy is the affective variant of strategy use and they both influence reading proficiency levels considerably (Boakye, 2015a). High self-efficacy promotes metacognitive awareness and contributes to reading proficiency.…”
Section: Self-efficacy In Readingmentioning
confidence: 99%
“…These factors among others are the students' self-efficacy, reading homework, and high reading, then followed by teaching method, reading frequency at home, and after reading activities. Self-efficacy is the belief that students can take action or succeed in certain situations, in this case being able to read comprehensively [55]. People with high self-efficacy are more likely to view difficult tasks as something that must be mastered because he is very confident with their abilities and does not try to avoid the tasks given to him [56]- [58].…”
Section: Literacy: Some Notionsmentioning
confidence: 99%
“…Studies have shown that when learners are motivated to read, they are able to make casual inferences and comprehend the implications of the text more fully (Guthrie & Wigfield, 1999). Boakye (2015) states that learners with high self-efficacy levels are motivated to persist for longer, put in more effort and strive to complete a given task.…”
Section: Reading Motivation and Reading Comprehension Achievementmentioning
confidence: 99%
“…Reading, according to Boakye (2011), is a multifaceted skill involving social, affective and cognitive processes. This self-efficacy building strategy was focused on exploiting his actual experience and extant knowledge (Bandura, 1993;Boakye, 2015). His successful attempts to read the first paragraph without giving up made him realise that he was within his zone of ability to read (Vygotsky, 2011: 208) and this new awareness motivated him to read the rest of the comprehension passage.…”
Section: Self-efficacy and Reading Motivationmentioning
confidence: 99%